Catalytic graphitizing agent, carbon sheet for gas diffusion layer and preparation method of carbon sheet
By using asphalt-loaded boron-based catalyst catalytic graphitizer in carbon sheets, the problems of insufficient conductivity of carbon sheets and high energy consumption in the graphitization process are solved, and efficient conductive performance improvement and cost savings are achieved.
Patent Information
- Application Number
- CN202510040390.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The carbon sheets in the existing gas diffusion layer are insufficient in conductivity, resulting in a decrease in the working efficiency of fuel cells, and at the same time, the high-temperature graphitization process consumes energy and costs.
By loading the boron-based catalyst on the asphalt surface, composite particles are formed, and the interface optimization effect of the asphalt is used during the hot pressing and graphitization process, the micromorphology of the resin carbon and the conductivity of the carbon sheet are improved.
The conductive properties of the carbon sheet and its produced gas diffusion layer are improved, the graphitization temperature and energy consumption are reduced, and the production cost is saved.
Smart Images

Figure CN119591100A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell gas diffusion layers, and in particular to a catalytic graphitization agent, a carbon sheet for a gas diffusion layer and a preparation method thereof. Background Art
[0002] In recent years, proton exchange membrane fuel cell technology, which uses hydrogen and oxygen as energy sources, has developed rapidly as a green energy technology that utilizes hydrogen energy. The gas diffusion layer is an important component of the membrane electrode, the core component of the fuel cell. It is located between the catalyst layer and the bipolar plate. In the operation of the fuel cell, it plays a role in coordinating the exchange of water and gas phases, exporting waste heat from electrochemical reactions, conducting electricity between the cathode and anode, and providing mechanical support for the catalyst layer.
[0003] The current gas diffusion layer mainly uses a two-dimensional carbon sheet with carbon fiber and resin carbon as the main components as the substrate, on which the microporous layer is loaded. The preparation process of the carbon sheet as the substrate mainly includes papermaking, impregnation, curing, graphitization, etc. The specific process is as follows: the chopped carbon fiber is made into a native carbon sheet through the papermaking process; the native carbon sheet is loaded with resin through the resin impregnation process to make an impregnated carbon sheet; then through the curing process, the impregnated carbon sheet is hot-pressed and cured to obtain a cured carbon sheet; finally, the cured carbon sheet is placed in a graphitization furnace for graphitization process, and the final carbon sheet as the substrate of the gas diffusion layer is obtained.
[0004] In the impregnation process of raw carbon sheets, the phenolic resin system has the advantages of low cost, good processability, high graphitization residual carbon rate, and good bonding performance of the resin carbon generated by graphitization, so phenolic resin is usually used as the main component in the resin impregnation solution. However, the chemical structure of phenolic resin determines that it is difficult to form resin carbon with a high degree of graphitization in the graphitization process, and its disordered structure is difficult to rearrange to form an ordered graphitized crystal structure during high-temperature graphitization treatment, thereby restricting the conductivity of the resin carbon formed by phenolic resin, which is not conducive to the conductivity of carbon sheets. The reduction in the conductivity of carbon sheets will increase the internal resistance of the fuel cell membrane electrode assembly, affect the ohmic polarization effect, and ultimately lead to a reduction in the working efficiency of the fuel cell.
[0005] In addition, the commonly used graphitization temperature of resin carbon is in the range of 1800-2800℃. As the graphitization temperature increases, the energy consumption and the manufacturing cost of the graphitization furnace also increase significantly. Therefore, reducing the maximum graphitization temperature as much as possible can greatly save the equipment and energy costs of the graphitization process.
[0006] In order to improve the graphitization degree of phenolic resin carbon and the conductivity of carbon sheets, and obtain phenolic resin carbon with a higher graphitization degree at a lower graphitization temperature, a feasible method is to introduce a catalytic graphitizing agent into the resin system and then perform graphitization. However, most catalysts with catalytic graphitization properties will form metal cations during the operation of the fuel cell, causing fuel cell pollution and irreversible performance degradation. Boron-based catalytic graphitizing agents will not cause fuel cell pollution, so such catalysts can be used to homogenize the resin carbon at high temperature to catalyze the graphitization process of phenolic resin carbon, thereby reducing the performance requirements of the graphitization furnace equipment, reducing the graphitization energy consumption, and saving costs.
[0007] However, in practical applications, boron-based catalytic graphitization agents will cause the surface of phenolic resin carbon to become rougher after graphitization, which will lead to poor interface between resin carbon and carbon fiber in carbon sheets and high contact resistance.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] The first purpose of the present invention is to provide a catalytic graphitization agent. By loading a boron catalyst on the surface of asphalt and controlling the ratio of the two, during the hot pressing and graphitization process, the molten asphalt can fill the interface between the boron catalyst and other components, exerting the interface optimization effect of asphalt, and can solve the problems of rough micromorphology of resin carbon, poor interface between resin carbon and carbon fiber in carbon sheet, and large contact resistance caused by the use of boron catalyst alone, thereby improving the conductive properties of carbon sheet. In addition, compared with phenolic resin, asphalt is a carbon precursor that is more prone to graphitization reaction. The introduction of asphalt can further improve the conductive properties of carbon sheet.
[0010] The second purpose of the present invention is to provide a method for preparing a catalytic graphitizing agent based on mechanical grinding. This method utilizes the property of low softening point asphalt that is easy to melt under mechanical action. The boron-based catalyst is loaded on the asphalt surface through mechanical grinding. It has the advantages of simple process, easy operation and low equipment cost.
[0011] The third object of the present invention is to provide a carbon sheet for a gas diffusion layer, which can catalyze the graphitization reaction of phenolic resin carbon by adding a catalytic graphitizing agent containing asphalt and a boron catalyst, and reduce the microscopic roughness of the resin carbon, solve the problem of poor interface between the resin carbon and the carbon fiber and large contact resistance, thereby improving the conductivity of the carbon sheet for the gas diffusion layer. In addition, the use of the catalytic graphitizing agent can improve the graphitization degree of the resin carbon part in the carbon sheet, while reducing the requirements for the performance of the graphitization furnace equipment in the production of the carbon sheet, reducing the graphitization energy consumption, and reducing the production cost.
[0012] The fourth object of the present invention is to provide a method for preparing a carbon sheet for a gas diffusion layer. The carbon sheet for a gas diffusion layer prepared by this method has good electrical conductivity, and the method is simple to operate, has a short process flow, and has low production cost.
[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0014] The present invention first provides a catalytic graphitization agent, which is a composite particle with a boron catalyst loaded on the surface of asphalt; wherein the mass ratio of the asphalt to the boron catalyst is 2 to 20:1.
[0015] Furthermore, the softening point of the asphalt is 80-120°C.
[0016] Furthermore, the coking value of the asphalt is 30% to 60%.
[0017] Furthermore, the toluene insoluble matter content in the asphalt is 5 wt.% to 40 wt.%.
[0018] Furthermore, the content of quinoline insoluble matter in the asphalt is less than 10 wt.%.
[0019] Furthermore, the particle size of the asphalt is ≤100 μm.
[0020] Furthermore, the asphalt includes at least one of natural asphalt, petroleum asphalt, coal asphalt and modified asphalt.
[0021] Furthermore, the boron-based catalyst includes at least one of boron element, boron carbide and boron nitride.
[0022] Furthermore, the average particle size of the boron-based catalyst is 0.5 to 10 μm.
[0023] The present invention further provides a method for preparing the catalytic graphitization agent, comprising the following steps: mixing asphalt and a boron-based catalyst and mechanically grinding the mixture so that the boron-based catalyst is loaded on the surface of the asphalt.
[0024] Furthermore, the softening point of the asphalt is 80-120°C; the mechanical grinding method includes ball milling, and the operating conditions of the ball milling include: (1) the ball milling equipment includes a planetary ball mill, and the rotation speed of the equipment is 300-1000rpm; (2) the ball milling is dry ball milling; (3) the ball milling uses a zirconia ball milling jar and grinding balls, the ball-to-material ratio in the ball milling is 1:1-6:1, and the diameter of the grinding balls is 1-15mm; (4) the ball milling method includes intermittent ball milling, and the intermittent ball milling method specifically includes: each ball milling is 3-15min, and the machine is stopped for cooling for 2-10min, and the ball milling and cooling process is repeated 10-40 times.
[0025] The present invention further provides a carbon sheet for a gas diffusion layer, which is mainly made of a resin impregnation liquid and a native carbon sheet; wherein the resin impregnation liquid is mainly composed of the catalytic graphitizing agent and phenolic resin in a mass ratio of 1 to 15:15 to 45.
[0026] Furthermore, the resin impregnation solution includes the following components in parts by mass: 0.1 to 1.5 parts of the catalytic graphitization agent, 1.5 to 4.5 parts of the phenolic resin, 0.01 to 0.2 parts of the anti-settling agent and 2 to 10 parts of the solvent; wherein the anti-settling agent includes at least one of polyvinyl pyrrolidone, polyurea and polyamide wax.
[0027] Furthermore, the phenolic resin includes thermosetting phenolic resin.
[0028] The present invention also provides a method for preparing the carbon sheet for the gas diffusion layer, comprising the following steps: impregnating a native carbon sheet with a resin impregnation liquid and then drying to obtain an impregnated carbon sheet; hot pressing and curing the impregnated carbon sheet to obtain a cured carbon sheet; and graphitizing the cured carbon sheet to obtain the carbon sheet for the gas diffusion layer.
[0029] Furthermore, the method for preparing the native carbon sheet comprises: mixing chopped carbon fibers and a dispersion medium to obtain chopped carbon fiber slurry, and then making sheets and drying the chopped carbon fiber slurry.
[0030] Furthermore, the temperature of the hot pressing is 100-180°C.
[0031] Furthermore, the hot pressing pressure is ≤5Mpa.
[0032] Furthermore, the hot pressing time is 2 to 120 minutes.
[0033] Furthermore, the graphitization temperature is 1600-2400°C.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The catalytic graphitization agent provided by the present invention is a catalyst that is loaded onto the surface of asphalt. During the hot pressing and graphitization process of the composite particles, the molten asphalt can fill the interface between the boron catalyst and other components, thereby playing the role of asphalt in optimizing the interface. This can solve the problems of rough microstructure of resin carbon, poor interface between resin carbon and carbon fiber in carbon sheets, and large contact resistance caused by the use of boron catalysts alone, thereby improving the electrical conductivity of carbon sheets and gas diffusion layers made therefrom.
[0036] (2) The catalytic graphitization agent provided by the present invention can improve the graphitization degree of the resin carbon part in the carbon sheet, reduce the requirements for the performance of the graphitization furnace equipment in the production of carbon sheets, and reduce the graphitization energy consumption and production cost.
[0037] (3) The catalytic graphitization agent provided by the present invention can further reduce the resistivity of the carbon sheet and improve the conductivity of the carbon sheet while ensuring the carbonization rate by controlling the mass ratio of the asphalt and the boron-based catalyst.
[0038] (4) The catalytic graphitizing agent provided by the present invention utilizes the property of low softening point asphalt that is easy to melt during mechanical grinding. The melted asphalt can act as an adhesive, so that the boron catalyst particles are loaded on the surface of the asphalt particles to form a microscopic composite structure. The mechanical grinding method is low in cost and simple in equipment, and avoids the problem of solvent use that is more common in other composite methods.
[0039] (5) The catalytic graphitization agent provided by the present invention can produce a carbon sheet for a gas diffusion layer with low plane resistivity and vertical resistivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 A schematic flow chart of a method for preparing a carbon sheet for a gas diffusion layer provided by the present invention;
[0042] Figure 2 An optical microscope image of the asphalt used in Example 1 provided by the present invention;
[0043] Figure 3 An optical microscope image of the catalytic graphitizing agent prepared in Example 1 provided by the present invention;
[0044] Figure 4 An optical microscope image of the carbon sheet for gas diffusion layer prepared in Example 1 provided by the present invention;
[0045] Figure 5 An optical microscope image of the carbon sheet for a gas diffusion layer prepared in Comparative Example 1 provided by the present invention;
[0046] Figure 6 An optical microscope image of the carbon sheet for a gas diffusion layer prepared in Comparative Example 2 provided by the present invention;
[0047] Figure 7This is an optical microscope image of the carbon sheet for gas diffusion layer prepared in Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION
[0048] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If the specific conditions are not indicated in the embodiments, they are carried out according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0049] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0050] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0051] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0052] In a first aspect, the present invention provides a catalytic graphitization agent, which is a composite particle with a boron-based catalyst loaded on the surface of asphalt.
[0053] The mass ratio of the asphalt and the boron-based catalyst is 2 to 20:1, including but not limited to any one of 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, and 20:1, or a range between any two of the above.
[0054] The catalytic graphitization agent provided by the present invention loads a boron catalyst on the surface of asphalt. During the hot pressing and graphitization process of the composite particles, the molten asphalt can fill the interface between the boron catalyst and other components, thereby playing the interface optimization role of the asphalt. It can solve the problems of rough microscopic morphology of resin carbon, poor interface between resin carbon and carbon fiber in carbon sheets, and large contact resistance caused by the use of boron catalysts alone, and improve the conductivity of carbon sheets and gas diffusion layers made therefrom.
[0055] The catalytic graphitizing agent provided by the present invention can catalyze the graphitization reaction of phenolic resin carbon in the graphitization process. The catalytic graphitizing agent is used to prepare a fuel cell gas diffusion layer. By catalyzing the graphitization reaction of the resin carbon in the graphitization treatment stage by the catalytic graphitizing agent, the purpose of optimizing the performance of the carbon sheet for the fuel cell gas diffusion layer can be achieved.
[0056] Specifically, asphalt, as a graphite precursor material, has the advantages of high residual carbon rate, good residual carbon conductivity and improved interface effect. In addition, the physical and chemical properties of asphalt itself, such as melting and graphitization behavior, are compatible with the existing carbon sheet manufacturing process (it can adapt to the process parameters of each process in the preparation of carbon sheets). Furthermore, asphalt itself is a carbon precursor that is easier to graphitize than phenolic resin, so the introduction of asphalt will not have an adverse effect on the conductive properties of the system itself.
[0057] At the same time, boron-based catalysts can catalyze the graphitization process of asphalt and phenolic resin, further improving the catalyst effect.
[0058] Furthermore, the use of the catalytic graphitization agent can improve the graphitization degree of the resin carbon part in the carbon sheet, and can also reduce the requirements for the performance of the graphitization furnace equipment in the production of the carbon sheet, and reduce the graphitization energy consumption and production cost.
[0059] Furthermore, the present invention can further reduce the resistivity of the carbon sheet and improve the electrical conductivity of the carbon sheet while ensuring the carbonization rate by controlling the mass ratio of the asphalt and the boron-based catalyst.
[0060] In some specific embodiments, the softening point of the asphalt is 80-120°C, including but not limited to any one of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and 120°C, or any range between two of them. Asphalt with a low softening point is easy to melt during grinding, and the melted asphalt can act as a binder, so that the boron catalyst particles are loaded on the surface of the asphalt particles to form composite particles, avoiding the common problem of solvent use in other composite methods.
[0061] In some specific embodiments, the coking value of the asphalt is 30% to 60%, including but not limited to any one of 30%, 35%, 40%, 45%, 55%, 60% or any range between two thereof. It is understood that the coking value is related to the softening point.
[0062] In some specific embodiments, the toluene insoluble matter content in the asphalt is 5wt.% to 40wt.%, including but not limited to any point value of 5wt.%, 10wt.%, 15wt.%, 20wt.%, 25wt.%, 30wt.%, 35wt.%, 40wt.%, or any range value between two of them. Among them, the toluene insoluble matter is mainly macromolecular asphaltenes, which have a great positive effect on the graphitization process of asphalt.
[0063] In some specific embodiments, the content of quinoline insoluble matter in the asphalt is less than 10wt.%, including but not limited to any one of 9wt.%, 8wt.%, 7wt.%, 6wt.%, 5wt.%, 4wt.%, 3wt.%, 1wt.%, or any range between two of them. The quinoline insoluble matter is mainly a difficult-graphitization component, and its content is controlled at a relatively low level, which is beneficial to improving the performance of the catalytic graphitization agent.
[0064] In some specific embodiments, the particle size of the asphalt is ≤ 100 μm, including but not limited to any point value of 100 μm, 80 μm, 60 μm, 50 μm, 30 μm, 20 μm, 10 μm, 5 μm, 1 μm or any range value between two of them. If the particle size of the asphalt is too large, the stability of the resin impregnation liquid will decrease; if the particle size of the asphalt is too small, the pre-treatment process of the asphalt powder, including crushing and screening, will be more complicated and time-consuming.
[0065] In some specific embodiments, the asphalt is crushed and sieved.
[0066] In some specific embodiments, the asphalt includes at least one of natural asphalt, petroleum asphalt, coal asphalt and modified asphalt. The modified asphalt includes but is not limited to naphthalene modified asphalt, rubber modified asphalt or thermoplastic resin modified asphalt, etc., which is not limited in the present invention.
[0067] In some specific embodiments, the boron-based catalyst includes at least one of boron, boron carbide and boron nitride.
[0068] The boron catalyst is preferably boron carbide. When boron carbide is used, it can act as a grinding aid and lubricant during the grinding process, thereby improving the grinding efficiency.
[0069] In some specific embodiments, the average particle size (i.e., Dv50 particle size) of the boron catalyst is 0.5 to 10 μm, including but not limited to any point value of 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or a range value between any two of them. If the particle size of the boron catalyst is too small, it is difficult to load it onto the asphalt surface during grinding; and if the particle size is too large, even close to the particle size of asphalt particles, it is difficult to form a microscopic composite structure.
[0070] In a second aspect, the present invention provides a method for preparing the catalytic graphitization agent, comprising the steps of: mixing asphalt and a boron-based catalyst and mechanically grinding the mixture so that the boron-based catalyst is loaded on the surface of the asphalt to obtain the catalytic graphitization agent.
[0071] The preparation method of the catalytic graphitization agent provided by the present invention comprises the following steps: modifying the boron catalyst by introducing asphalt, and allowing the boron catalyst particles to adhere to the surface of the asphalt particles after mechanical grinding. During the hot pressing and graphitization process of this microscopic composite structure, the molten asphalt can fill the interface between the boron catalyst and other components, thereby playing the interface optimization role of the asphalt, thereby solving the problems of rough microscopic morphology of resin carbon, poor interface between resin carbon and carbon fiber in carbon sheets, and large contact resistance caused by the use of boron catalysts alone, thereby improving the electrical conductivity of the carbon sheets and the gas diffusion layers prepared therefrom.
[0072] In addition, the method has the advantages of simple process, short flow, easy operation, low equipment cost and suitability for mass production.
[0073] In some specific embodiments, the softening point of the asphalt is 80-120°C, including but not limited to any one of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or a range between any two of them.
[0074] By utilizing the property of low softening point asphalt that is easy to melt during grinding, the melted asphalt under grinding can act as a binder, so that the boron catalyst particles are loaded on the surface of the asphalt particles to form a catalytic graphitizer with a microscopic composite structure. This method can avoid the common problem of solvent use in other composite methods and further reduce production costs.
[0075] In some specific embodiments, the mechanical grinding method includes but is not limited to ball milling.
[0076] The powder mixture of asphalt and boron catalyst should be subjected to dry mechanical grinding with appropriate intensity (the intensity is determined by the parameters such as the rotation speed, time, and structure of the equipment components of the grinding equipment). If the grinding intensity is too high, the prepared catalytic graphitization agent will be sticky and agglomerated; if the grinding intensity is too low, it is difficult for the boron catalyst to be loaded onto the asphalt surface through the micro-melting of the asphalt during grinding, and an effective micro-composite structure cannot be formed.
[0077] The present invention takes the ball milling method as an example, and the range of its operating conditions is as follows: (1) the equipment of the ball milling method is a planetary ball mill, and the equipment rotation speed is 300 to 1000 rpm, such as 500 rpm, 600 rpm or 800 rpm; (2) the ball milling method is dry ball milling; (3) the ball milling method uses a zirconia ball milling jar and grinding balls, the ball-to-material ratio in the ball milling is in the range of 1:1 to 6:1, such as 3:1, 4:1 or 5:1, and the diameter of the grinding balls is in the range of 1 to 15 mm. For example, 3mm, 5mm, 8mm, 10mm or 13mm; (4) the ball milling method includes intermittent ball milling, and the intermittent ball milling method specifically includes: each ball milling time is 3 to 15 minutes (for example, 5 minutes, 6 minutes, 8 minutes, 10 minutes or 12 minutes), and the machine is stopped for cooling for 2 to 10 minutes (for example, 3 minutes, 5 minutes or 8 minutes), and the ball milling and cooling process is repeated 10 to 40 times (for example, 15 times, 20 times, 30 times or 35 times).
[0078] During the grinding process, by controlling parameters such as grinding time and grinding intensity, and setting intervals during grinding to allow the sample in the equipment to be fully cooled, it is possible to ensure that the boron catalyst is loaded on the surface of the asphalt particles. If the grinding time is too long, the grinding intensity is too high, or the cooling is insufficient, the asphalt will undergo a large-scale fusion phenomenon during grinding, making the sample lumpy; while if the grinding time and intensity are too low, it will be difficult to load the boron catalyst on the surface of the asphalt particles.
[0079] In a third aspect, the present invention provides a carbon sheet for a gas diffusion layer, which is mainly made of a resin impregnation solution and a native carbon sheet.
[0080] Wherein, the resin impregnation liquid is mainly composed of the catalytic graphitizing agent and the phenolic resin in a mass ratio of 1 to 15:15 to 45. Wherein, the mass ratio of the catalytic graphitizing agent to the phenolic resin includes but is not limited to any one of 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 5:15, 5:20, 5:25, 5:30, 5:35, 5:40, 5:45, 10:15, 10:20, 10:25, 10:30, 10:35, 10:40, 10:45, 15:15, 15:20, 15:25, 15:30, 15:35, 15:40, 15:45, or any range value between any two of them.
[0081] The present invention can catalyze the graphitization reaction of phenolic resin carbon and reduce the microscopic roughness of the resin carbon by adding a catalytic graphitizing agent containing asphalt and a boron-based catalyst, thereby solving the problems of poor interface between the resin carbon and carbon fiber and large contact resistance, thereby reducing the resistivity of the carbon sheet, improving the conductivity of the carbon sheet for the gas diffusion layer, and reducing energy consumption and production costs.
[0082] At the same time, the present invention controls the ratio of the catalytic graphitizing agent and the phenolic resin, which is beneficial to improving the homogeneous graphitization effect of the catalytic graphitizing agent on the resin carbon, catalyzing the graphitization process of the phenolic resin carbon, and improving the graphitization degree of the phenolic resin carbon and the conductive properties of the carbon sheet for the gas diffusion layer.
[0083] In some specific embodiments, in order to further improve the graphitization degree of phenolic resin carbon and the conductivity of carbon sheets for gas diffusion layers, the resin impregnation solution includes the following components in parts by mass: 0.1 to 1.5 parts of the catalytic graphitization agent, 1.5 to 4.5 parts of phenolic resin, 0.01 to 0.2 parts of anti-settling agent and 2 to 10 parts of solvent.
[0084] Wherein, the catalytic graphitizing agent includes, but is not limited to, any one of 0.1 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.3 parts, 1.5 parts or any range between two parts by weight; the phenolic resin includes, but is not limited to, any one of 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 4.3 parts, 4.5 parts or any range between two parts by weight; the anti-settling agent includes, but is not limited to, any one of 1.5 parts, 1.8 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 4.3 parts, 4.5 parts or any range between two parts by weight; The amounts in parts by mass include but are not limited to any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, or any range between two of them; the amounts in parts by mass include but are not limited to any one of 2, 3, 4, 4.5, 5, 5.8, 6, 6.5, 7, 7.5, 8, 8.5, 9, 10, or any range between two of them.
[0085] Among them, the main function of the anti-settling agent is to maintain the stability of the catalytic graphitization agent in the resin impregnation liquid system and optimize the effect of the resin impregnation process.
[0086] In some specific embodiments, the phenolic resin comprises a thermosetting phenolic resin.
[0087] In some specific embodiments, the free phenol content of the phenolic resin is 10% to 20%, including but not limited to any one of 10%, 12%, 13%, 15%, 18%, 20% or a range between any two of them.
[0088] In some specific embodiments, the solid content of the phenolic resin is 40% to 70%, including but not limited to any point value of 40%, 45%, 50%, 55%, 60%, 65%, 70% or a range value between any two of them.
[0089] In some specific embodiments, the anti-settling agent includes at least one of polyvinyl pyrrolidone, polyurea and polyamide wax.
[0090] In some specific embodiments, the solvent includes an organic solvent, such as at least one of methanol, ethanol, isopropanol and toluene, but is not limited thereto.
[0091] In a fourth aspect, the present invention provides a method for preparing the carbon sheet for the gas diffusion layer, or a method for catalytic graphitization of the carbon sheet for the gas diffusion layer of a fuel cell, comprising the following steps: impregnating the raw carbon sheet with a resin impregnation liquid and then drying to obtain an impregnated carbon sheet; hot pressing and curing the impregnated carbon sheet to obtain a cured carbon sheet; graphitizing the cured carbon sheet, and cooling to obtain the carbon sheet for the gas diffusion layer. The resin impregnation liquid is mainly composed of the catalytic graphitization agent and phenolic resin in a mass ratio of 1 to 15:15 to 45.
[0092] The preparation method of the carbon sheet for gas diffusion layer provided by the present invention is simple to operate, has a short process flow, is suitable for mass production, and has low production cost. In addition, the carbon sheet for gas diffusion layer prepared by the method has good electrical conductivity.
[0093] In some specific embodiments, the preparation method of the native carbon sheet includes wet papermaking, and the wet papermaking method specifically includes: mixing short-cut carbon fibers and a dispersion medium to obtain short-cut carbon fiber slurry, using a sheeting machine to make sheets, and then drying.
[0094] Figure 1 A schematic flow chart of a method for preparing a carbon sheet for a gas diffusion layer provided by the present invention.
[0095] In some specific embodiments, the chopped carbon fiber includes at least one of polyacrylonitrile-based carbon fiber, asphalt-based carbon fiber and viscose-based carbon fiber.
[0096] In some specific embodiments, the average length of the chopped carbon fiber is 1 to 20 mm, including but not limited to any point value of 1 mm, 3 mm, 5 mm, 8 mm, 10 mm, 12 mm, 15 mm, 17 mm, and 20 mm, or a range value between any two of them; the average diameter of the chopped carbon fiber is 1 to 15 μm, including but not limited to any point value of 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, and 15 μm, or a range value between any two of them.
[0097] In some specific embodiments, the surface density of the raw carbon sheet is 15 to 60 g / m 2 ; Including but not limited to 15g / m 2 , 20g / m 2 , 25g / m 2 , 30g / m 2 , 35g / m 2 , 40g / m 2 , 45g / m 2 , 50g / m 2 , 60g / m 2 Any point value in or any range of values between them.
[0098] In some specific embodiments, the average thickness of the native carbon sheet is 120-600 μm, including but not limited to any point value of 120 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm or a range value between any two of them.
[0099] In some specific embodiments, the dispersion medium comprises water.
[0100] In some specific implementations, the chopped carbon fiber slurry is prepared using a high-speed dispersing device.
[0101] In some specific embodiments, the impregnation time in the impregnation process is 10 to 300 s, including but not limited to any point value of 10 s, 30 s, 50 s, 80 s, 100 s, 150 s, 200 s, 250 s, 300 s, or a range value between any two of them.
[0102] In some specific embodiments, the drying temperature in the impregnation process is 60-150°C, including but not limited to any point value of 60°C, 70°C, 80°C, 100°C, 120°C, 130°C, 150°C or any range value between two of them.
[0103] In some specific embodiments, the drying time in the dipping process is 1 to 30 minutes, including but not limited to any one of 1 minute, 3 minutes, 5 minutes, 8 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, or a range between any two of them.
[0104] In some specific embodiments, the hot pressing temperature is 100-180°C, including but not limited to any point value of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 180°C or a range between any two of them.
[0105] In some specific embodiments, the hot pressing pressure is ≤5 MPa, including but not limited to any point value of 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa or a range value between any two of them.
[0106] In some specific embodiments, the hot pressing time is 2 to 120 min, including but not limited to any one of 2 min, 3 min, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 60 min, 80 min, 90 min, 100 min, and 120 min, or a range between any two of them.
[0107] In some specific embodiments, the hot pressing equipment includes but is not limited to a flat vulcanizing press.
[0108] In some specific embodiments, the graphitization temperature is 1600-2400°C, including but not limited to any point value of 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C or any range value between two thereof. The preparation method of the carbon sheet for gas diffusion layer provided by the present invention can obtain phenolic resin carbon with a high degree of graphitization at a lower graphitization temperature by adding a catalytic graphitization agent during the preparation process. The obtained carbon sheet for gas diffusion layer has good conductivity, low energy consumption and low production cost.
[0109] In some specific implementations, the graphitization time is determined by the heating rate and the final temperature during the graphitization process, and may be, for example, 16 min to 240 min, but is not limited thereto.
[0110] In some specific embodiments, the heating rate of graphitization is 10 to 100°C / min, including but not limited to any point value of 10°C / min, 20°C / min, 30°C / min, 40°C / min, 50°C / min, 60°C / min, 70°C / min, 80°C / min, 90°C / min, and 100°C / min, or a range value between any two of them.
[0111] In some specific embodiments, the graphitization atmosphere includes an inert atmosphere, such as argon or nitrogen.
[0112] In some specific embodiments, the graphitization equipment includes but is not limited to a graphitization furnace.
[0113] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0114] Example 1
[0115] The preparation method of the catalytic graphitizing agent provided in this embodiment comprises the following steps: using a medium-temperature coal tar pitch with a softening point of 85°C, a coking value of 45.6%, a toluene insoluble content of 9.5wt.%, and a quinoline insoluble content of 0.2wt.%, using a blade crusher to crush the coal tar pitch, and then sieving to obtain a coal tar pitch powder with a particle size of ≤100μm. Boron carbide powder with an average particle size of 2μm is used as a boron catalyst. Coal tar pitch powder and boron carbide powder are weighed according to a mass ratio of 6:1, and the two powders are mixed and mechanically ground using a ball mill. The grinding equipment is a planetary ball mill, the speed of the planetary ball mill is 800rpm, the ball milling is dry ball milling, the ball mill and the grinding ball are made of zirconium oxide, the ball-to-material ratio is 3:1, and the diameter of the grinding ball is 4mm. Grind for 5min each, stop cooling for 3min, repeat the grinding-cooling process 12 times, and obtain a catalytic graphitizing agent. The catalytic graphitization agent comprises composite particles, wherein the composite particles comprise asphalt and a boron-based catalyst supported on the surface of the asphalt. Figure 2 FIG. 1 is an optical microscope image of the asphalt used in Example 1 after being crushed and sieved; Figure 3 The optical microscope image of the catalytic graphitization agent prepared in Example 1 is shown. Figure 2 and Figure 3 It can be seen that through the mechanical grinding method, part of the white crystal particles of boron carbide are loaded on the surface of the black asphalt particles under the melting effect of asphalt, forming a catalytic graphitization agent with a micro-composite structure.
[0116] The method for preparing the carbon sheet for the gas diffusion layer provided in this embodiment comprises the following steps:
[0117] (1) Chopped polyacrylonitrile-based carbon fibers with an average length of 4 mm and an average diameter of 7 μm were used. Water was used as a dispersion medium. The carbon fibers were dispersed by a high-speed dispersion device to obtain a slurry. After being made into sheets using a sheet making machine, the slurry was dried at 100° C. for 30 min to obtain a surface density of 25 g / m 2 , native carbon sheets with an average thickness of 240μm.
[0118] (2) According to the mass fraction, 6 parts of ethanol (solvent) are weighed, and then 3 parts of thermosetting phenolic resin are added to the ethanol under stirring, and then 0.1 parts of polyurea anti-settling agent are added, and finally 0.6 parts of the above-prepared catalytic graphitizing agent (i.e., the mass ratio of catalytic graphitizing agent to phenolic resin is 6:30) are added, and then the mixed solution is dispersed using a dispersing disk mixer to obtain a resin impregnation liquid. Then, the raw carbon sheet obtained in step (1) is immersed in the resin impregnation liquid for 120 seconds, taken out and dried at 100° C. for 10 minutes to obtain an impregnated carbon sheet.
[0119] (3) The impregnated carbon sheet obtained in step (2) is hot-pressed and cured in a flat vulcanizer, wherein the temperature, pressure and time of the hot-pressing are 140° C., 4 MPa and 30 min, respectively, to obtain a cured carbon sheet.
[0120] (4) Under the protection of argon, the cured carbon sheet obtained in step (3) is heated to 2000° C. at a heating rate of 15° C. / min for graphitization to obtain a carbon sheet that can be used for a gas diffusion layer or a gas diffusion layer substrate of a fuel cell.
[0121] like Figure 4 The optical microscope image of the carbon sheet for gas diffusion layer prepared in Example 1 is shown.
[0122] Example 2
[0123] The preparation method of the catalytic graphitizing agent provided in this embodiment is basically the same as that in Example 1, except that the coal tar pitch is replaced by petroleum asphalt with a softening point of 120°C, a coking value of 55.4%, a toluene insoluble content of 13.1wt.%, and a quinoline insoluble content of 0.4wt.%.
[0124] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0125] Example 3
[0126] The preparation method of the catalytic graphitizing agent provided in this embodiment is basically the same as that in Example 1, except that the coal tar pitch is replaced by a naphthalene-modified asphalt having a softening point of 115°C, a coking value of 50.4%, a toluene insoluble content of 18.1wt.%, and a quinoline insoluble content of 0.4wt.%.
[0127] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0128] Example 4
[0129] The preparation method of the catalytic graphitization agent provided in this embodiment is basically the same as that in Embodiment 1, except that boron carbide is replaced by a boron element with an average particle size of 5 μm.
[0130] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0131] Example 5
[0132] The preparation method of the catalytic graphitizing agent provided in this embodiment is basically the same as that in Embodiment 1, except that boron carbide is replaced by boron nitride with an average particle size of 10 μm.
[0133] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0134] Example 6
[0135] The preparation method of the catalytic graphitization agent provided in this embodiment is basically the same as that in embodiment 1, except that the rotation speed of the grinding equipment is 600 rpm, the ball mill and grinding balls used are made of zirconium oxide, the ball-to-material ratio is 3:1, and the diameter of the grinding balls is 4 mm. Each grinding is 3 minutes, and the machine is stopped for cooling for 3 minutes, and the grinding-cooling process is repeated 10 times.
[0136] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0137] Example 7
[0138] The preparation method of the catalytic graphitizing agent provided in this embodiment is basically the same as that in Example 1, except that the mass ratio of coal tar pitch powder to boron carbide powder is replaced with 15:1.
[0139] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0140] Example 8
[0141] The preparation method of the catalytic graphitizing agent provided in this embodiment is basically the same as that in Embodiment 1, except that the mass ratio of coal tar pitch powder to boron carbide powder is replaced to 3:1.
[0142] The catalytic graphitization agent prepared in this example was used to prepare a carbon sheet for a gas diffusion layer according to the method for preparing a carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0143] Example 9
[0144] The preparation method of the catalytic graphitization agent provided in this embodiment is the same as that in Example 1.
[0145] The method for preparing the carbon sheet for gas diffusion layer provided in this embodiment is basically the same as that in Example 1, except that in step (2), the amount of the catalytic graphitizing agent added is replaced with 0.3 parts (ie, the mass ratio of the catalytic graphitizing agent to the phenolic resin is 3:30).
[0146] Example 10
[0147] The preparation method of the catalytic graphitization agent provided in this embodiment is the same as that in Example 1.
[0148] The method for preparing the carbon sheet for gas diffusion layer provided in this embodiment is basically the same as that in Example 1, except that in step (2), the amount of the catalytic graphitizing agent added is replaced with 1.2 parts (i.e., the mass ratio of the catalytic graphitizing agent to the phenolic resin is 12:30).
[0149] Comparative Example 1
[0150] The preparation method of the carbon sheet for gas diffusion layer provided in this comparative example is basically the same as that of Example 1, except that in step (2), no catalytic graphitizing agent is added, and the amount of thermosetting phenolic resin added is replaced by 3.6 parts.
[0151] Comparative Example 2
[0152] The preparation method of the catalytic graphitization agent provided in this comparative example is the same as that of Example 1.
[0153] The preparation method of the carbon sheet for gas diffusion layer provided in this comparative example is basically the same as that of Example 1, except that in step (2), the catalytic graphitizing agent is replaced by an equal mass of boron carbide powder with an average particle size of 2 μm.
[0154] Comparative Example 3
[0155] The preparation method of the catalytic graphitization agent provided in this comparative example is the same as that of Example 1.
[0156] The preparation method of the carbon sheet for gas diffusion layer provided in this comparative example is basically the same as that of Example 1, except that in step (2), the catalytic graphitizing agent is replaced by an equal mass of the coal tar powder prepared in Example 1.
[0157] Comparative Example 4
[0158] The preparation method of the catalytic graphitizing agent provided in this comparative example is basically the same as that in Example 1, except that the coal tar pitch is replaced by a coal tar pitch having a softening point of 160°C, a coking value of 66.4%, a toluene insoluble content of 33.1wt.%, and a quinoline insoluble content of 11.3wt.%.
[0159] The catalytic graphitization agent prepared in this comparative example was used to prepare a carbon sheet for a gas diffusion layer according to the preparation method of the carbon sheet for a gas diffusion layer in Example 1 to prepare a carbon sheet for a gas diffusion layer.
[0160] Experimental example
[0161] According to the test standard GB / T20042.7-2014, proton exchange membrane fuel cell part 7: carbon paper property test method, the performance of the carbon sheet for gas diffusion layer obtained in the above embodiments and comparative examples was tested, and the plane resistivity and vertical resistivity of the carbon sheet for gas diffusion layer were calculated, and the carbonization rate was calculated as follows: mass of carbon sheet for gas diffusion layer / mass of carbon sheet after curing × 100%. The test results are shown in Table 1.
[0162] Table 1 Carbonization rate, plane resistivity and vertical resistivity results
[0163] Group Carbonization rate (%) Plane resistivity (mΩ·cm) Vertical resistivity (mΩ·cm) Example 1 67.9 8.57 515 Example 2 66.5 9.88 496 Example 3 66.8 8.67 520 Example 4 68.1 8.30 531 Example 5 68.3 9.44 591 Example 6 68.1 9.19 657 Example 7 65.9 10.48 580 Example 8 69.7 9.22 722 Example 9 66.8 9.77 540 Example 10 68.2 9.34 550 Comparative Example 1 68.6 12.53 588 Comparative Example 2 72.6 9.54 934 Comparative Example 3 64.3 11.33 595 Comparative Example 4 71.7 9.24 747
[0164] It can be seen from Table 1 that each embodiment has a lower resistivity.
[0165] Specifically, Comparative Example 1 can be used as a control group, where pitch and boron carbide are not added, and the resin component is mainly phenolic carbon sheet performance. In Example 1, a catalytic graphitization agent composited with pitch and boron carbide is used, and its plane resistivity and vertical resistivity are significantly improved compared with Comparative Example 1, especially the improvement of plane resistivity is the most obvious.
[0166] Example 10 uses a larger proportion of catalytic graphitizing agent than Example 1, but its conductivity is slightly worse than that of Example 1; Example 9 uses a smaller proportion of catalytic graphitizing agent than that of Example 1, and its conductivity is slightly worse than that of Example 1, indicating that the amount of catalytic graphitizing agent used will have a certain effect on the planar resistivity and vertical resistivity of the carbon sheet for the gas diffusion layer.
[0167] In Example 8, the ratio of asphalt to boron carbide was reduced and the amount of boron carbide was increased. It was found that the vertical resistance increased significantly compared with that in Example 1, indicating that when the boron carbide content is too high, the asphalt cannot effectively fill the interface and the problem of poor contact resistance still exists.
[0168] In Example 7, the ratio of coal tar pitch to boron carbide was increased, and it was found that both the vertical resistance and the plane resistance increased compared with those in Example 1, indicating that the amount of boron carbide used was too small to effectively catalyze graphitization.
[0169] Comparative Example 2 is a solution in which boron carbide is simply added. Its carbonization rate is higher than that of Example 1, which illustrates the catalytic graphitization effect of boron carbide. The addition of boron carbide significantly optimizes the planar resistance, but causes a significant deterioration in the vertical resistance, which illustrates the problem of poor interface and contact resistance caused by the boron-based catalyst.
[0170] Comparative Example 3 is a solution in which asphalt is simply added, and its conductive performance is relatively close to that of Comparative Example 1. The lower carbonization rate is because the carbonization rate of asphalt is lower than that of phenolic resin.
[0171] Comparative Example 4 uses asphalt with too high a softening point. Since the asphalt with a high softening point is difficult to trigger micro-melting during grinding to form a microscopic composite structure with the boron catalyst, it is impossible to optimize the interface problem and contact resistance problem of the boron catalyst.
[0172] In addition, the optical microscope image of the carbon sheet for gas diffusion layer prepared in Example 1 is shown in FIG. Figure 4 The optical microscope image of the carbon sheet for gas diffusion layer prepared in Comparative Example 1 is shown in Figure 5 ; Comparative Example 2 obtained gas diffusion layer carbon sheet optical microscope image see Figure 6 ; Comparative Example 3 obtained gas diffusion layer carbon sheet optical microscope image see Figure 7 .
[0173] It can be seen that Figure 5 In Comparative Example 1, the surface of the phenolic resin carbon without adding boron carbide and asphalt is relatively smooth. This is because no boron catalyst is added in Comparative Example 1, and thus there is no problem of rough surface of the phenolic resin carbon. Figure 7 In Comparative Example 3, the resin carbon with asphalt added has some pores on its surface due to the decomposition of asphalt during the graphitization process. Figure 4 Example 1 and Comparative Example 2 Figure 6 It can be seen that the catalytic graphitizer with a composite structure can improve the roughness of the resin carbon to a certain extent, thereby achieving the effect of optimizing the interface and contact resistance.
[0174] In summary, the present invention utilizes the properties of low softening point asphalt that is easy to melt during mechanical grinding and the properties of asphalt as a graphitized carbon precursor, and cooperates with the catalytic effect of boron catalysts in the resin graphitization process. By compounding asphalt and boron catalysts and controlling the ratio of the two, the problems of rough resin carbon, poor interface, and poor contact resistance when using boron catalysts alone are improved. This method can catalyze the graphitization process of resin carbon in the graphitization process, optimize the plane and vertical surface conductivity of carbon sheets for gas diffusion layers, reduce the graphitization temperature, and achieve the purpose of saving equipment and graphitization energy consumption costs.
[0175] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A catalytic graphitization agent, characterized in that: The catalytic graphitization agent is a composite particle with a boron-based catalyst loaded on the surface of asphalt; Wherein, the mass ratio of the asphalt to the boron-based catalyst is 2 to 20:
1.
2. The catalytic graphitization agent according to claim 1, characterized in that: At least one of the following conditions is met: (1) The softening point of the asphalt is 80 to 120°C; (2) The coking value of the asphalt is 30% to 60%; (3) The toluene insoluble matter content in the asphalt is 5 wt.% to 40 wt.%; (4) the content of quinoline insoluble matter in the asphalt is less than 10 wt.%; (5) The particle size of the asphalt is ≤100 μm; (6) The asphalt includes at least one of natural asphalt, petroleum asphalt, coal asphalt and modified asphalt.
3. The catalytic graphitization agent according to claim 1, characterized in that: At least one of the following conditions is met: (1) The boron-based catalyst comprises at least one of boron element, boron carbide and boron nitride; (2) The average particle size of the boron-based catalyst is 0.5 to 10 μm.
4. The method for preparing the catalytic graphitization agent according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing asphalt and a boron catalyst and mechanically grinding the mixture, so that the boron catalyst is loaded on the surface of the asphalt.
5. The method for preparing the catalytic graphitizing agent according to claim 4, characterized in that: The softening point of the asphalt is 80-120°C.
6. The method for preparing the catalytic graphitization agent according to claim 4, characterized in that: The mechanical grinding method includes ball milling, and the operating conditions of the ball milling include: (1) the ball milling equipment includes a planetary ball mill, and the rotation speed of the equipment is 300 to 1000 rpm; (2) the ball milling is dry ball milling; (3) the ball milling uses a zirconia ball milling jar and grinding balls, the ball-to-material ratio in the ball milling is 1:1 to 6:1, and the diameter of the grinding balls is 1 to 15 mm; (4) the ball milling method includes intermittent ball milling, and the intermittent ball milling method specifically includes: each ball milling time is 3 to 15 minutes, and the machine is stopped for cooling for 2 to 10 minutes, and the ball milling and cooling process is repeated 10 to 40 times.
7. A carbon sheet for a gas diffusion layer, characterized in that: It is mainly made of resin impregnation liquid and raw carbon sheet; The resin impregnation liquid is mainly composed of the catalytic graphitization agent according to any one of claims 1 to 3 and phenolic resin in a mass ratio of 1 to 15:15 to 45.
8. The carbon sheet for gas diffusion layer according to claim 7, characterized in that: At least one of the following conditions is met: (1) The resin impregnation solution comprises the following components by weight: 0.1 to 1.5 parts of the catalytic graphitization agent, 1.5 to 4.5 parts of the phenolic resin, 0.01 to 0.2 parts of the anti-settling agent and 2 to 10 parts of the solvent; wherein the anti-settling agent comprises at least one of polyvinyl pyrrolidone, polyurea and polyamide wax; (2) The phenolic resin includes a thermosetting phenolic resin.
9. The method for preparing a carbon sheet for a gas diffusion layer according to claim 7 or 8, characterized in that: The following steps are involved: The raw carbon sheet is impregnated with a resin impregnation liquid and then dried to obtain an impregnated carbon sheet; Hot pressing and curing the impregnated carbon sheet to obtain a cured carbon sheet; The solidified carbon sheet is graphitized to obtain the carbon sheet for the gas diffusion layer.
10. The method for preparing a carbon sheet for a gas diffusion layer according to claim 9, characterized in that: At least one of the following conditions is met: (1) The method for preparing the raw carbon sheet comprises: mixing chopped carbon fibers and a dispersion medium to obtain chopped carbon fiber slurry, and then making sheets and drying them; (2) The temperature of the hot pressing is 100 to 180° C.; (3) The hot pressing pressure is ≤5 MPa; (4) The heat pressing time is 2 to 120 minutes; (5) The graphitization temperature is 1600-2400°C.
Citation Information
Patent Citations
Method for producing carbon cathode material of composite coated lithium ion battery
CN103441251A
Preparation method of carbon fiber paper for gas diffusion layer of fuel cell
CN119121695A
A process of production of carbon negative electrode material for lithium ion battery
WO2005055346A1